Odpowiedzi

2009-12-08T20:06:18+01:00
(3X+4)²
9x²+24+16

(6X+2)²
36x²+24+4

(2x-4)²
4x²-16x+16

(2y-5x)²
4y²-20x+25x²

(5a+2y)*(5a-2y)
25a²-4y²

(xy+4)*(xy-4)
x²y²-16
2009-12-08T20:07:53+01:00
(3X+4)² = 9x² + 2*3x*4 + 4² = 9x² + 24x + 16
(6X+2)² = 36x² + 2*6x*2 + 2² = 36x² + 24x + 4

(2x-4)² = 4x² - 2*4*2x + 4² = 4x² - 16x + 16
(2y-5x)² = 4y² - 2*2y*5x + 25x² = 4y² - 20xy + 25x²

(5a+2y)*(5a-2y) = (5a)² - (2y)² = 25a² - 4y²
(xy+4)*(xy-4) = (xy)² - 4² = x²y² - 16
2009-12-08T20:11:50+01:00
(3X+4)²=9x²+24x+16
(6X+2)²=36x²+24x+4
(2x-4)²=4x²-16x+16
(2y-5x)²=4y²-4y5x+25x
(5a+2y)*(5a-2y)=5a²-2y²=25a²-4y²
(xy+4)*(xy-4)=xy²-4²=x²y²-16